2006
DOI: 10.1158/0008-5472.can-05-4254
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-w Promotes Gastric Cancer Cell Invasion by Inducing Matrix Metalloproteinase-2 Expression via Phosphoinositide 3-Kinase, Akt, and Sp1

Abstract: Given a previous report that Bcl-w is expressed in gastric cancer cells, particularly in those of an infiltrative morphology, we investigated whether Bcl-w expression influences the invasiveness of gastric cancer cells. To accomplish this, Bcl-w was overexpressed in adherent types of gastric adenocarcinoma cell lines, and this was found to result in an increase in their migratory and invasive potentials. These effects were not induced when Bcl-2 was overexpressed in the same cell types. Consistently, Bcl-w, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
3
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 15 publications
7
123
3
1
Order By: Relevance
“…As ICAM-3 activated Akt in our previous study (26), we postulated these proteins were involved in increased cell migration and invasion by ICAM-3. In our results, inhibition of Akt suppressed activity/expression of MMP and cell migration/ invasion, which agree with previous results of Bae et al, Weng et al and Yoeli-Lerner et al that PI3 kinase/Akt promotes cell migration and invasion through the induction of MMP proteins and modulation of MMP expression, and they also indicated that treatment of LY294002 suppressed cell migration and invasion (27,29,30). Du and Montminy reported that CREB is located at downstream of Akt, which induced phosphorylation of Ser-133 of CREB and then stimulated expression of the target gene via the activation of CREB (35).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…As ICAM-3 activated Akt in our previous study (26), we postulated these proteins were involved in increased cell migration and invasion by ICAM-3. In our results, inhibition of Akt suppressed activity/expression of MMP and cell migration/ invasion, which agree with previous results of Bae et al, Weng et al and Yoeli-Lerner et al that PI3 kinase/Akt promotes cell migration and invasion through the induction of MMP proteins and modulation of MMP expression, and they also indicated that treatment of LY294002 suppressed cell migration and invasion (27,29,30). Du and Montminy reported that CREB is located at downstream of Akt, which induced phosphorylation of Ser-133 of CREB and then stimulated expression of the target gene via the activation of CREB (35).…”
Section: Discussionsupporting
confidence: 93%
“…2A and B). It was shown in several cancer types that various factors induced high expression MMP-2 and MMP-9; Ionizing radiation promote hepatocellular carcinoma cell invasion with increase of MMP-9 expression (4), enhancement of Bcl-2 expression increase gastric cancer cell invasion with increase of MMP-2 expression and activity (27), insulin-like growth factor-1 (IGF-1) induces invasion of distinct breast cancer cell lines (MDA-MB231, MDA-MB-435 and SUM-159-PT) with induction of MMP proteins (30), and hepatitis B viral HBx protein increase hepatocellular carcinoma invasion potential with induction of MMP-9 gene expression (31). Our results also defined the role of ICAM-3 as an inducer of MMP proteins, and it increased cell migration and invasion via increase of activities of MMP-2 and -9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reports have demonstrated that MMP-2 expression is critically mediated by MAPK members 13,15) and PI3K/Akt pathway. 23,33,34) MAPK and PI3K/Akt pathways also play an important role in endothelial cell viability, migration, and tube formation by specific stimuli. [13][14][15]25,35,36) Therefore, we examined the effect of a-chaconine on the activities of MAPK and PI3K/Akt signaling pathways.…”
Section: Fig 3 Effect Of A-chaconine On Chemotaxis and Invasion Of mentioning
confidence: 99%
“…19,20 Interestingly, it has been found that Sp1 can also induce the expression of many antiapoptotic genes (such as survivin, bcl-x, and bcl-w). 20,21 Moreover, several recent studies have indicated that the overexpression of Sp1 causes apoptotic cell death in nontransforming cells, but the downregulation of the overexpressed Sp1 protein in human fibrosarcoma cell lines inhibits tumor formation. 13,22 Therefore, the effect of Sp1 overexpression on apoptosis regulation in transforming cells remains controversial, and the detailed mechanism of this process remains unclear.…”
Section: Uiccmentioning
confidence: 99%